A Blueprint to Evaluate One Health - Rüegg, Simon R.; McMahon, Barry J.; Häsler, Barbara; Esposito, Roberto; Nielsen, Liza Rosenbaum; Ifejika Speranza, Chinwe; Ehlinger, Timothy; Peyre, Marisa; Aragrande, Maurizio; Zinsstag, Jakob; Davies, Philip; Mihalca, Andrei Daniel; et al. (Frontiers in Public Health, 2017)
One Health (OH) positions health professionals as agents for change and provides a platform to manage determinants of health that are often not comprehensively captured in medicine or public health alone. However, due to the organisation of societies and disciplines, and the sectoral allocation of resources, the development of transdisciplinary approaches requires effort and perseverance. Therefore, there is a need to provide evidence on the added value of OH for governments, researchers, funding bodies and stakeholders. This paper outlines a conceptual framework of what OH approaches can encompass and the added values they can provide. The framework was developed during a workshop conducted by the “Network for Evaluation of One Health”, an Action funded by the European Cooperation in Science and Technology. By systematically describing the various aspects of OH we provide the basis for measuring and monitoring the integration of disciplines, sectors and stakeholders in health initiatives. The framework identifies the social, economic and environmental drivers leading to integrated approaches to health, and illustrates how these evoke characteristic OH operations, i.e. thinking, planning and working, and require supporting infrastructures to allow learning, sharing and systemic organisation. It also describes the OH outcomes (i.e. sustainability, health and welfare, interspecies equity and stewardship, effectiveness and efficiency), which are not possible to obtain through sectoral approaches alone, and their alignment with aspects of sustainable development based on society, environment and economy.